The Effectiveness of Using Learning Videos on Student Science Learning Outcomes in Digital PR Courses - Fitriansyah, Fifit (IJIS Edu : Indonesian Journal of Integrated Science Education, 2023)
Effective learning should involve many elements of learning, one of which is the use of learning media.Looking back over the past 3 years, where the Covid 19 Pandemic has spread in every sector of life, theeducation sector is no exception. For this reason, after the Covid-19 pandemic, the way of learning that waspreviously done online has changed, now it is done offline again. As a result, various adjustments to face-to-face learning patterns are needed. One of the efforts to use learning media in the form of learning videosis a solution that helps lecturers deliver learning material. By combining audio and visual elements, learningvideos have the power to facilitate student learning to be more effective with its repeatable nature. Thepurpose of this study was to see the effectiveness of using learning videos on student learning outcomes inDigital PR courses. The research method used is quantitative descriptive analysis. The results of this studywere as many as 91% of students were helped by the learning videos used. Thus, the use of learning videosis considered effective in improving student learning outcomes with an average learning mastery of 93%.